Analysis of Directed Motivational Currents (DMC) in EFL Students' Reading Motivation - Nindia Dwi Citra Dwi; Fetriani; Washlurachim Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Motivation is a key determinant of success in learning English as a Foreign Language (EFL), particularly in reading, which requires sustained. concentration, strategic approaches, and perseverance. However, many students struggle to maintain reading motivation, highlighting the need for a framework that explains strong and sustained motivational engagement. Directed Motivational Currents (DMC) provides such a framework, offering insights into the triggers, sustaining mechanisms, and contextual influences on motivation. This study investigates the triggers and maintenance strategies of DMC, describes students' experiences within this motivational state, analyzes the impact of contextual and instructional factors, and explores its implications for engagement and long-term reading habit formation. This study employed a mixed-methods convergent design, data were collected from 14 fourth-semester students of the English Education Study Program through total sampling. The quantitative data were analyzed descriptively, while qualitative data underwent Interpretative Phenomenological Analysis (IPA). The findings indicate that DMC is triggered by both positive and negative experiences, social support, and tangible reading progress. Motivation is sustained through reading routines and incremental goal-setting. Students in DMC reported positive emotional engagement, a clear long-term vision, and structured behavioral patterns, though internalization levels varied. Classroom environment, teaching strategies, and peer and lecturer support were found critical in initiating and sustaining DMC. Keywords: Directed Motivational Currents (DMC), EFL Students, Reading Motivation, Reading Skills